Incidence, long-term predictors and progression of chronic kidney disease among African migrants and non-migrants: the transcontinental population-based prospective RODAM cohort study - Mungamba, Muhulo Muhau; Chilunga, Felix P; van der Linden, Eva L; Beune, Erik; Godwill, Engwa A; Hayfron-Benjamin, Charles F; Meeks, Karlijn; Darko, Samuel N; Twumasi-Ankrah, Sampson; Owusu-Dabo, Ellis; Vogt, Liffert; van den Born, Bert-Jan H; et al. (BMJ global health, 2025)
BackgroundLimited longitudinal data exist on chronic kidney disease (CKD) in African populations undergoing epidemiological transitions. We investigated incidence, long-term predictors and progression of CKD among Ghanaians residing in Ghana and Ghanaian migrants in the Netherlands (Amsterdam).Methods and findingsWe analysed data from 2183 participants in the transcontinental population-based prospective Research on Obesity and Diabetes among African Migrants cohort, followed for approximately 7 years. CKD incidence and its progression to end-stage kidney disease (ESKD) were defined using Kidney Disease: Improving Global Outcomes (KDIGO) criteria. CKD incidence was calculated using age- and sex standardisation for those without CKD at baseline. Long-term predictors of CKD incidence were identified using one-step robust Poisson regression. CKD progression to ESKD from baseline was also assessed using robust Poisson regressions. Overall age- and sex standardised CKD incidence was 11.0% (95% CI 9.3% to 12.3%) in the population, with Ghanaians residing in Amsterdam at (7.6%; 5.7% to 9.5%) and Ghanaians residing in Ghana at (12.9%; 10.9% to 14.9%). Within Ghana, rural Ghanaians had similar CKD incidence to urban Ghanaians (12.5%; 8.5% to 15.5% vs 12.3%; 8.2% to 15.8%). Residence in Amsterdam was associated with lower CKD incidence compared with Ghana after adjustments (incidence rate ratio=0.32; 0.13–0.77). CKD incidence predictors were advanced age, female sex, alcohol consumption, uric acid levels and hypertension. CKD progression to ESKD was 2.3% among Ghanaians residing in Ghana and 0.0% among Ghanaians residing in Amsterdam.ConclusionOne-tenth of Ghanaians developed CKD over 7 years, with higher incidence in Ghana compared with Europe. Age, female sex, alcohol use, uric acid levels and hypertension were predictive factors. CKD progression to ESKD was minimal. High CKD incidence among Ghanaians, especially those residing in Ghana, calls for in-depth assessment of contributing factors and targeted interventions.